Sejarah Perkembangan dan Peranan Multimedia Berbasis Dakwah Islamiah - Widi Arika Basri; Erwan Efendi; Ratna Dewi; Imam Pratama Gultom (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
The development and role of multimedia is the most effective and very influential preaching tool in life at this time, all people use this multimedia as their means to easily access all forms of activity. Islamic da'wah using multimedia is an attempt to invite and invite others to remain in the teachings of Allah SWT. This research is a study that carries out the history of the development of multimedia based on Islamic da'wah. The purpose of this research is so that we can understand, and how we can use multimedia well in conveying dawah messages. More than 63 million people in Indonesia use multimedia. Many preachers use this tool to spread da'wah, apart from being easy, of course listeners or mad'u are of course easy to digest da'wah messages. Keywords : development of multimedia, the role of multimedia, Islamic da'wah